The Correlation Between Writing Motivation and Writing Achievement - Dilia Juni Pratiwi; Aridah Aridah; Mardliya Pratiwi Zamruddin (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2022)
Motivation is an important element in learning, especially in writing. It can affect the achievement of learning. This study is conducted to analyze the correlation between students’ motivation and achievement in writing. The purposes of this study are : (1) to find out the level of writing motivation of the sixth semester students of English Department of Mulawarman University. (2) to find out the level of writing achievement of the sixth semester students of English Department of Mulawarman University. (3) to find out whether there is a correlation between writing motivation and writing achievement of the sixth semester students of English Department of Mulawarman University. The researcher utilized a correlational design in this study. The population of this study was taken from the sixth semester students of English Department, whereas this study used 25 students as the sample. The instruments of this study were Academic Writing Motivation Questionnaire and score documentation of Writing. This study used an analysis of Pearson Product Moment correlation to find out the result of hypotheses. There were three result of this study. First, based on the calculation of Academic Writing Motivation questionnaire, it was shown that the level of writing motivation of the sixth semester students of English Department of Mulawarman University was in low category. Second, the analysis of writing score documentation shown that the level of students’ writing achievement of the sixth semester of English Department of Mulawarman University was in low category. Third, based on the data ofwriting motivation and writing achievement, it was shown that r value is .902 with a significance value of .000 < 0.05, so Ho is rejected and Ha is accepted. It was assumed that writing motivation and writing achievement have a relationship.